Investigation of the evolution of nitrogen defects in flash-lamp-annealed InGaZnO films and their effects on transistor characteristics. (22nd May 2018) - Eom, Tae-Yil; Ahn, Chee-Hong; Kang, Jun-Gu; Salman, Muhammad Saad; Lee, Sun-Young; Kim, Yong-Hoon; Lee, Hoo-Jeong; Kang, Chan-Mo; Kang, Chiwon
Abstract: In this study, we show the evolution of nitrogen defects during a sol–gel reaction in flash-lamp-annealed InGaZnO (IGZO) films and their effects on the device characteristics of their thin-film transistors (TFTs). The flash lamp annealing (FLA) of the IGZO TFT for 16 s helps achieve a mobility of approximately 7 cm 2 V −1 s −1 . However, further extension of the annealing time results only in drastic increases in carrier concentration and off-current. The X-ray photoelectron spectroscopy (XPS) analysis of the N 1s peak unravels the presence of oxygen-vacancy-associated nitrogen defects and their evolution with annealing time, which is possibly responsible for the increase in carrier concentration.